Association of Serum Leptin with Gestational Diabetes Mellitus - Shaima Sultana Memon, Fizzah Ali, Soha Haque, Saadia Saad, Zafar Iqbal, Uzma Iftikhar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: It has been stated that leptin has a role in glucose regulation as it decreases the insulin resistance and regulates the insulin mediated glucose metabolism. As the body need more glucose, more secretion of insulin which stimulates adipose tissues to secrete more leptin which causes the release of cytokines which decreases insulin sensitivity and develop insulin resistance. The aim of the current study was to find out the association of serum leptin with gestational diabetes mellitus in current setting. Methods: A case control study was conducted at the Gynecology department of Abbasi Shaheed Hospital Karachi during April to September 2022. A self-designed proforma was used, consisting of 4 parts consisting of demographic variables, general physical examination and laboratory findings. Blood sample was collected during 24th to 28th week of gestation for testing fasting blood sugar, OGTT and then ELISA was done. Statistical Package for Social Science (SPSS) version-20 was used to analyze the data. p-value ≤0.05 was considered as significant. Results: The mean age of the study participants was 27.42 ± 0.39 and 24.96 ± 0.51 in cases and controls respectively. The basal metabolic index (BMI) was higher among the cases of gestational diabetes as compared to normal controls. Likewise, oral glucose tolerance test results showed higher levels of blood glucose than the normal controls during all steps of the test. The comparison of serum insulin and serum leptin during pregnancy and after delivery in cases of gestational diabetes showed a decrease in both serum insulin and serum leptin levels with significant p-value (p-value ≤0.05). Conclusion: Leptin is the contributory factor of insulin resistance and leads to gestational diabetes mellitus. Both serum insulin and serum leptin levels were having strong significant association with gestational diabetes mellitus. Keywords: Gestational diabetes mellitus, Serum Leptin, Hyperinsulinemia